Parametric Study Of Friction Stir Spot Welding (FSSW) For Polymer Materials Case Of High Density Polyethylene Sheets: Experimental And Numerical Study - Djilali Benyerou; El Bahri Ould Chikh; Habib Khellafi; Hadj Miloud Meddah; Ali Benhamena; Kaddour Hachelaf; Abdellah Lounis (Fracture and Structural Integrity)
Friction stir spot welding (FSSW) is a very important part of conventional friction stir welding (FSW) which can be a replacement for riveted assemblies and resistance spot welding. This technique provides high quality joints compared to conventional welding processes. Friction stir spot welding (FSSW) is a new technology adopted to join various types of metals such as titanium, aluminum, magnesium. It is also used for welding polymer materials which are difficult to weld by the conventional welding process. In various industrial applications, high density polyethylene (HDPE) becomes the most used material. The parameters and mechanical properties of the welds are the major problems in the welding processes. In this paper, we have presented a contribution in finite element modeling of the friction stir spot welding process (FSSW) using Abaqus as a finite element solver. The objective of this paper is to study the HDPE plates resistance of stir spot welding joints (FSSW). First, we show the experimental tests results of high-density polyethylene (HDPE) plates assembled by friction stir spot welding (FSSW). Three-dimensional numerical modeling by the finite element method makes it possible to determine the best representation of the weld joint for a good prediction of its behavior. Comparison of the results shows that there is a good agreement between the numerical modeling predictions and the experimental results.